Uji Cemaran dan Identifikasi Bakteri Staphylococcus aureus pada Bumbu Giling di Pasar Tradisional Kota Samarinda - Aisyah Mutia Iskandar; Supri Hartini; Sresta Azahra; Tiara Dini Harlita (Yayasan Literasi Sains Indonesia, 2026)
Ground spice paste is a widely consumed food product sold in traditional markets with varying environmental conditions. Differences between wet and dry stalls may affect environmental sanitation and the microbiological safety of the product, including contamination by Staphylococcus aureus. This study aimed to determine the Total Plate Count (TPC) and identify S. aureus in cooked ground spice pastes sold in traditional markets in Samarinda City. A descriptive observational study was conducted using 12 samples consisting of rendang, soup, and rawon spice pastes collected from wet and dry stalls. TPC was determined using the pour plate method on Plate Count Agar (PCA), while S. aureus was identified using Mannitol Salt Agar (MSA) followed by biochemical tests. Environmental sanitation conditions were assessed through direct observation, and the data were analyzed descriptively. The results showed that all samples met acceptable organoleptic criteria; however, several samples exceeded the maximum TPC limit established by SNI 7388:2009 and were contaminated with S. aureus. Samples exceeding the maximum TPC limit were more frequent in wet stalls (83.3%) than in dry stalls (66.7%), with the highest count found in rendang spice paste. Meanwhile, S. aureus was detected more frequently in wet stalls (50.0%) than in dry stalls (33.3%). The higher descriptive proportions of microbiological contamination in wet stalls coincided with poorer sanitation conditions, including standing water, high humidity, and open storage. These findings indicate that cooked ground spice pastes sold in traditional markets are susceptible to microbiological contamination, particularly in stalls with inadequate sanitation.